Clinical courses and outcomes of five patients with primary lung cancer surgically treated while affected by Severe acute respiratory syndrome coronavirus 2. (28th August 2020) - Gonfiotti, Alessandro; Gatteschi, Lavinia; Salvicchi, Alberto; Bongiolatti, Stefano; Lavorini, Federico; Voltolini, Luca
Abstract: OBJECTIVES: There is currently a lack of clinical data on the novel beta-coronavirus infection [caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2)] and concomitant primary lung cancer. Our goal was to report our experiences with 5 patients treated for lung cancer while infected with SARS-CoV-2. METHODS: We retrospectively evaluated 5 adult patients infected with SARS-CoV-2 who were admitted to our thoracic surgery unit between 29 January 2020 and 4 March 2020 for surgical treatment of a primary lung cancer. Clinical data and outcomes are reported. RESULTS: All patients were men with a mean age of 74.0 years (range 67–80). Four of the 5 patients (80%) reported chronic comorbidities. Surgery comprised minimally invasive lobectomy (2 patients) and segmentectomy (1 patient), lobectomy with en bloc chest wall resection (1 patient) and pneumonectomy (1 patient). Mean chest drain duration was 12.4 days (range 8–22); mean hospital stay was 33.8 days (range 21–60). SARS-CoV-2-related symptoms were fever (3 patients), persistent cough (3 patients), diarrhoea (2 patients) and syncope (2 patients); 1 patient reported no symptoms. Morbidity related to surgery was 60%; 30-day mortality was 40%. Two patients (1 with a right pneumonectomy, 74 years old; 1 with a lobectomy with chest wall resection and reconstruction, 70 years old), developed SARS-CoV-2-related lung failure leading to death 60 and 32 days after surgery, respectively. CONCLUSIONS: Lung cancer surgery may represent a high-risk factor for developing a severe case of coronavirus disease 2019, particularly in patients with advanced stages of lung cancer. Additional strategies are needed to reduce the risk of morbidity and mortality from SARS-CoV-2 infection during treatment for lung cancer.